δ13C decreases in the upper western South Atlantic during Heinrich Stadials 3 and 2 ... : δ</ i> < sup> 13</ sup> C تنخفض في الجزء العلوي الغربي من جنوب المحيط الأطلسي خلال ملاعب هاينريش 3 و 2 ... - Marília de Carvalho Campos; Cristiano Mazur Chiessi; Ines Voigt; Alberto Piola; Henning Kuhnert; Stefan Mulitza (OpenAlex, 2017)
Abstract. Abrupt millennial-scale climate change events of the last deglaciation (i.e. Heinrich Stadial 1 and the Younger Dryas) were accompanied by marked increases in atmospheric CO2 (CO2atm) and decreases in its stable carbon isotopic ratios (δ13C), i.e. δ13CO2atm, presumably due to outgassing from the ocean. However, information on the preceding Heinrich Stadials during the last glacial period is scarce. Here we present δ13C records from two species of planktonic foraminifera from the western South Atlantic that reveal major decreases (up to 1 ‰) during Heinrich Stadials 3 and 2. These δ13C decreases are most likely related to millennial-scale periods of weakening of the Atlantic meridional overturning circulation and the consequent increase (decrease) in CO2atm (δ13CO2atm). We hypothesise two mechanisms that could account for the decreases observed in our records, namely strengthening of Southern Ocean deep-water ventilation and weakening of the biological pump. Additionally, we suggest that air–sea gas ... : الملخص. كانت أحداث تغير المناخ المفاجئة على نطاق الألفية في التآكل الأخير (أي هاينريش ستاديال 1 ودرياس الأصغر) مصحوبة بزيادات ملحوظة في ثاني أكسيد الكربون في الغلاف الجوي (CO2atm) وانخفاضات في نسب نظائر الكربون المستقرة (δ 13C)، أي δ 13CO2atm، ويرجع ذلك على الأرجح إلى إطلاق الغازات من المحيط. ومع ذلك، فإن المعلومات عن ملاعب هاينريش السابقة خلال الفترة الجليدية الأخيرة نادرة. هنا نقدم سجلات δ 13C من نوعين من المنخربات العوالق من غرب جنوب المحيط الأطلسي التي تكشف عن انخفاضات كبيرة (تصل إلى 1 ‰) خلال هاينريش ستاديالز 3 و 2. من المرجح أن تكون هذه الانخفاضات في δ 13C مرتبطة بفترات الألفية من ضعف دوران الانقلاب الطولي الأطلسي وما يترتب على ذلك من زيادة (انخفاض) في CO2atm (δ 13CO2atm). نفترض آليتين يمكن أن تفسر الانخفاضات الملحوظة في سجلاتنا، وهما تعزيز تهوية المياه العميقة في المحيط الجنوبي وإضعاف المضخة البيولوجية. بالإضافة إلى ذلك، نقترح أن تبادل الغاز بين الهواء والبحر يمكن أن يكون قد ساهم في انخفاض δ 13C الملحوظ. جنبًا إلى جنب مع خطوط الأدلة الأخرى، تتوافق بياناتنا مع الفرضية القائلة بأن ثاني أكسيد الكربون ...